A construção do espaço mítico em D. Aquino Corrêa, Silva Freire e Gabriel de Mattos - Amorim, Moisés Carlos de (2014)
In this academic work, the process of building the regional space in of D. Aquino Corrêa Silva Freire and Gabriel de Mattos works is investigated. Each author is representative and active in his generation, and designs an artistic language that recreates myths using archetypal images, in which space is poetically reconstituted, consolidating Mato Grosso's peculiar traces. Since the rise of regionalist conception in the early twentieth century, with Don Francisco de Aquino Corrêa, some concern with local identity is noticed, intertwining in the literary work a number of important elements such as: the nature, conquerors, the city, food, people, language, culture etc., in short, all the surrounding reality that populate the art imaginary . These elements, symbolically translated, that demonstrate the artist's worldview, reflecting the range of images that interpret and build the space, to emphasize the man's relationship with his "world", both in poetry and in prose. In these two possibilities of creation, we use the imaginary Gilbert Durand theory, based on the concept of myth analisys, for understanding the mythèmes that cover and recognize the particularities of each work, as well as the similarities between the thinking of the authors and process by which becomes a recurring experience in cosmicized space, which, in the twentieth century poetry, more specifically until the 50s, is the image of the paradise or the "Great Mother"; and, in the twenty-first century writing, becomes the place where the ritual transformation of being occurs, allowing a mythical aura of historical knowledge, of everyday living and the relationship between man and space.